Sila "Ketuhanan Yang Maha Esa” Sebagai Spirit Perjumpaan dan Persaudaraan dalam Konteks Pluralitas Agama di Indonesia - Samho, Bartolomeus (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
This qualitative research aims to describe the philosophical values of the Principle of Belief in the One, Supreme God as the spirit of encounter and brotherhood in the context of religious plurality in Indonesia. The philosophical values in the first Principle, in addition to having a vertical dimension, also have a horizontal dimension. The vertical dimension is related to the human tendency to seek wholeness in God, while the horizontal dimension is related to the implications of faith in the practice of life, namely noble and commendable behavior towards fellow human beings. The findings of this study indicate that the philosophical values of the Principle of Belief in the One, Supreme God do not provide room for religious egoism in various forms of expression. The conclusion is that the principle of Belief in One, Supreme God strengthens encounter and brotherhood in the context of religious plurality in Indonesia. Relevant attitudes of faith to the Principle, horizontally, are being humble, open to plurality, respecting other religions, recognizing equal rights to religious freedom, and rejecting all forms of radical-extreme actions in the form of destructive actions in the name of God and religion. Discriminatory, intolerant, and exclusive attitudes in the practice of religious life in Indonesia are contrary to the principle of Belief in the One, Supreme God.AbstrakPenelitian dengan metode kualitatif ini bertujuan untuk mendeskripsikan nilai-nilai filosofis Sila Ketuhanan Yang Maha Esa sebagai spirit perjumpaan dan persaudaraan dalam konteks pluralitas agama di Indonesia. Nilai-nilai filosofis dalam Sila pertama tersebut selain berdimensi vertikal, juga berdimensi horizontal. Dimensi vertikal berkaitan dengan kecenderungan manusia untuk mencari keutuhan diri kepada Tuhan, sedangkan dimensi horizontal berkaitan dengan implikasi iman dalam praksis kehidupan, yakni perilaku mulia dan terpuji kepada sesama manusia. Temuan penelitian ini menunjukkan bahwa nilai-nilai filosofis Sila Ketuhanan Yang Maha Esa tidak memberi ruang bagi egoisme agama dalam berbagai bentuk pengungkapannya. Kesimpulan penelitian ini adalah bahwa Sila ”Ketuhanan yang Maha Esa” memperkuat perjumpaan dan persaudaraan dalam konteks pluralitas agama di Indonesia. Sikap iman yang relevan dengan Sila tersebut, secara horizontal, adalah  rendah hati, terbuka pada pluralitas, menghormati agama lain, mengakui kesetaraan hak atas kebebasan beragama, dan menolak segala bentuk tindakan radikal-ekstrem berupa aksi-aksi destruktif atas nama Tuhan dan agama. Sikap diskriminatif, intoleran, dan eksklusif dalam praksis kehidupan beragama di Indonesia bertentangan dengan Sila Ketuhanan Yang Maha Esa.